Β‐cyclodextrin in personal care formulations: role on the complexation of malodours causing molecules. (18th March 2015) - Lopedota, A.; Cutrignelli, A.; Laquintana, V.; Franco, M.; Donelli, D.; Ragni, L.; Tongiani, S.; Denora, N.
Synopsis Objective The aim of this study was to prove the capability of β‐cyclodextrin (β‐CD) to interact with some representative molecules responsible to cause body malodour, such as carboxylic acids, thiols and steroids, present in sweat and body secretions. Methods The association constants in guest‐CD were determined by 1H‐NMR spectroscopy for thiols and steroids such as 3‐mercapto‐1‐hexanol, androstenone, androstenol and androsterone, and pH‐potentiometric titration for acetic acid, l(+) lactic acid, isobutyric acid, isovaleric acid and 3‐hydroxy‐3‐methyl‐hexanoic acid. Results All considered systems are able to interact with relatively weak association constants with β‐cyclodextrin, in a 1 : 1 host–guest ratio. Conclusion From these findings, it is possible to conclude that β‐CD is capable to interact with different components present in the sweat and body secretion, forming inclusion complexes. For this reason, β‐CD could be a component of body care formulations, such as deodorants.